2012
DOI: 10.1371/journal.pone.0045103
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Statistical Properties of Open Reading Frames in Bacterial Genomes

Abstract: An analytical model based on the statistical properties of Open Reading Frames (ORFs) of eubacterial genomes such as codon composition and sequence length of all reading frames was developed. This new model predicts the average length, maximum length as well as the length distribution of the ORFs of 70 species with GC contents varying between 21% and 74%. Furthermore, the number of annotated genes is predicted with high accordance. However, the ORF length distribution in the five alternative reading frames sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…when 'mother gene' is conserved there is some tendency for conservation in the alternative strand (Wichmann and Ardern, 2019), but it is suggestive of a kind of purifying selection where mutations to biochemically similar amino acids are preferred in a subset of embedded antisense ORFs. It has previously been shown that long antisense ORFs appear more often in natural genomes than expected based on codon composition of annotated coding genes (Mir et al, 2012), another hint of selective processes preserving some antisense ORFs.…”
Section: Evolution and Constraint In Antisense Proteinsmentioning
confidence: 98%
“…when 'mother gene' is conserved there is some tendency for conservation in the alternative strand (Wichmann and Ardern, 2019), but it is suggestive of a kind of purifying selection where mutations to biochemically similar amino acids are preferred in a subset of embedded antisense ORFs. It has previously been shown that long antisense ORFs appear more often in natural genomes than expected based on codon composition of annotated coding genes (Mir et al, 2012), another hint of selective processes preserving some antisense ORFs.…”
Section: Evolution and Constraint In Antisense Proteinsmentioning
confidence: 98%
“…The longest coding exons in vertebrates and genes in bacteria are GC-rich, whereas the shortest genes are GC-poor [158]. The low GC bacterium Mycoplasma mycoides (GC content =24%) has 1,106 genes, and most of the genes have less than 20 codons [159]. Fusobacterium is associated with human oral cavities.…”
Section: B Gc Content Psc Frequency and Gene Lengthmentioning
confidence: 99%
“…Silby & Levy, 2008;Tunca et al, 2009;Cheregi et al, 2012). However, the length distribution of overlapping open reading frames in bacteria suggest more of such genes exist (Mir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%